Efektivitas Program Shalat Tahajud Dalam Membentuk Kedisiplinan Santri di Pondok Pesantren Mahasiswa UNSIQ Jawa Tengah di Wonosobo Tahun 2024 - Aulia Agnis Sabila; Ngarifin Shiddiq; Vava Imam Agus Faisal (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The aims of this research are: 1) To find out more about the implementation of the tahajjud prayer program UNSIQ Central Java School Student Islamic in Wonosobo; 2) To determine the effectiveness of the tahajjud prayer program Wonosobo in forming student discipline at the UNSIQ Central Java Student Islamic Boarding School in Wonosobo; 3) To determine the supporting and inhibiting factors for the implementation of tahajjud prayers at the UNSIQ Central Jawa Atudent Islamic Boarding School in Wonosobo. This research was conducted using a qualitative descriptive research methodology, specifically focused on field research. Interviews, observation and documentation are the approaches used in data collection procedures. Data sources include students, boarding school administrators, and caregivers. Data reduction, data presentation, and drawing conclusions are the data analysis techniques used. The results of the research show that: (1) There are two procedures for carrying out the tahajjud prayer at the UNSIQ Student Islamic Boarding School. During the month of Ramadan it is carried out in congregation; outside of this time, it is done individually. (2) The tahajjud prayer program at the UNSIQ Student Islamic Boarding School is useful in fostering and forming a disciplined attitude towards time management, enforcing rules, worship and discipline. (3) Supporting factors for implementing the tahajjjud prayer at the UNSIQ Student Islamic Boarding School include awareness of students, cooperation between caregivers and boarding school administrators in providing support and understanding of the importance of the tahajud prayer, as well as the role of peers. Meanwhile, inhibiting factors include students inadequate understanding, less strategic toilet locations, unstable sleep schedules for students, and the impact of unpredictable weather changes.